2021
DOI: 10.3390/ijerph18052730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 48-Day Home Quarantine during the Covid-19 Pandemic on the First Outdoor Running Session among Recreational Runners in Spain

Abstract: COVID-19-induced quarantine may lead to deleterious effects on health status as well as to impaired performance and increased injury risk when re-starting training after lockdown. We investigated the physical activity (PA) habits of recreational runners in Spain during a 48-day home quarantine during the COVID-19 pandemic and the characteristics of the first outdoor running session after confinement. A cross-sectional study, including a self-reported running questionnaire completed after the first outdoor runn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This might be linked to training load management errors, since peaks in load can lead to injury, especially in the amateur population [ 37 ]. Mosqueira-Ourens et al [ 19 ] recorded the characteristics of the first outdoor running session after quarantine. They observed that advanced runners who covered longer distances during quarantine were capable of coping with the load in the first outdoor running session without pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be linked to training load management errors, since peaks in load can lead to injury, especially in the amateur population [ 37 ]. Mosqueira-Ourens et al [ 19 ] recorded the characteristics of the first outdoor running session after quarantine. They observed that advanced runners who covered longer distances during quarantine were capable of coping with the load in the first outdoor running session without pain.…”
Section: Discussionmentioning
confidence: 99%
“…This circumstance could be interpreted as an opportunity generated by lockdowns for non-exercisers to begin a regular exercise routine [ 18 ]. An inverse association between the collateral effects of home confinement and the training volume prior to and during lockdown was concluded in Spanish recreational runners according to a study investigating the effects of a 48-day home quarantine on the first outdoor running session [ 19 ]. Considering the published data, intensity-related and weight-bearing exercises were the most practiced during lockdown (75%), with more than 60% of people training on their own [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, during spring 2020 of the COVID-19 pandemic, youth long-distance runners reported a decrease in their running habits, including reduced running distance (decreased 14.0%), total number of runs per week (decreased 14.0%), and number of hard runs per week (decreased 27.0%) (Bazett-Jones et al, 2020). This is in contrast with adult runners that reportedly increased their running behaviors following social distancing restrictions (DeJong et al, 2021;Holmes et al, 2021;Mosqueira-Ourens et al, 2021). Adults who made more changes to their running behaviors were injured more but these changes were due to multiple factors (Holmes et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…This was also to avoid the collapse in world health systems and prevent the death of many. [5] . Consequently, the COVID-19-induced quarantine caused a drastic reduction in levels of physical activity in adults and children as well.…”
Section: Introductionmentioning
confidence: 99%